2002
DOI: 10.1074/jbc.m205941200
|View full text |Cite
|
Sign up to set email alerts
|

GADD153-mediated Anticancer Effects of N-(4-Hydroxyphenyl)retinamide on Human Hepatoma Cells

Abstract: The anticancer effects of N-(4-hydroxyphenyl)-retinamide (4HPR), a potential chemopreventive or chemotherapeutic retinamide, are thought to be derived from its ability to induce apoptosis. However, the mechanism of apoptosis induced by 4HPR remains unclear. Thus, this study was designed to identify the gene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 44 publications
5
63
0
Order By: Relevance
“…Mechanistic studies indicate that ROS induction is a prerequisite for proapoptotic activity and emphasize the importance of the intrinsic (mitochondrial) apoptosis pathway in mediating cell killing (Jing et al, 1999;Hail and Lotan, 2000;Wu et al, 2001;Miller et al, 2002;Simeone et al, 2002;Vuky et al, 2002;Li et al, 2003). These investigations and a number of others document several interesting parallels between how ROS inducers and mda-7/IL-24 kills various tumor cells, including pancreatic tumor cells following ablation of K-ras (Su et al, 2001) or treatment with ARS, HPR or NSC (Delia et al, 1995;Jing et al, 1999;Hail and Lotan, 2000;Wu et al, 2001;Kim et al, 2002;Miller et al, 2002;Simeone et al, 2002;Vuky et al, 2002;Xia et al, 2002;Zou et al, 2002;Lebedeva et al, 2003b;Li et al, 2003). Apoptosis induced by Ad.mda-7 in 'permissive' prostate, melanoma and malignant glioma cells and in 'resistant' pancreatic cancer cells (simultaneously treated with K-ras antisense phosphorothioate oligonucleotides) results in alterations in the ratio of antiapoptotic (such as Bcl-2 and Bcl-x L ) and proapoptotic (including Bax and Bak) proteins, changes in cell cycle resulting in accumulation of cells in the G 2 /M phase and upregulation in expression of the growth arrest and DNA damage inducible (GADD) gene family (Su et al, 2001Lebedeva et al, 2002Lebedeva et al, , 2003aSarkar et al, 2002b).…”
Section: Discussionmentioning
confidence: 95%
“…Mechanistic studies indicate that ROS induction is a prerequisite for proapoptotic activity and emphasize the importance of the intrinsic (mitochondrial) apoptosis pathway in mediating cell killing (Jing et al, 1999;Hail and Lotan, 2000;Wu et al, 2001;Miller et al, 2002;Simeone et al, 2002;Vuky et al, 2002;Li et al, 2003). These investigations and a number of others document several interesting parallels between how ROS inducers and mda-7/IL-24 kills various tumor cells, including pancreatic tumor cells following ablation of K-ras (Su et al, 2001) or treatment with ARS, HPR or NSC (Delia et al, 1995;Jing et al, 1999;Hail and Lotan, 2000;Wu et al, 2001;Kim et al, 2002;Miller et al, 2002;Simeone et al, 2002;Vuky et al, 2002;Xia et al, 2002;Zou et al, 2002;Lebedeva et al, 2003b;Li et al, 2003). Apoptosis induced by Ad.mda-7 in 'permissive' prostate, melanoma and malignant glioma cells and in 'resistant' pancreatic cancer cells (simultaneously treated with K-ras antisense phosphorothioate oligonucleotides) results in alterations in the ratio of antiapoptotic (such as Bcl-2 and Bcl-x L ) and proapoptotic (including Bax and Bak) proteins, changes in cell cycle resulting in accumulation of cells in the G 2 /M phase and upregulation in expression of the growth arrest and DNA damage inducible (GADD) gene family (Su et al, 2001Lebedeva et al, 2002Lebedeva et al, , 2003aSarkar et al, 2002b).…”
Section: Discussionmentioning
confidence: 95%
“…97 Several studies have shown that 4HPR and its analog induce CHOP expression in different types of cancer cells, which plays a role in 4HPR-induced apoptosis. [98][99][100][101][102][103] Therefore, these data suggest that 4HPR induces CHOP-dependent DR5 expression.…”
Section: Modulation Of Death Receptor Expression By Cancer Therapeutimentioning
confidence: 86%
“…Increased generation of reactive oxygen species (ROS) (Delia et al, 1997;Suzuki et al, 1999;Hail and Lotan, 2001), increased ceramide production (Maurer et al, 1999), induction of mitochondrial permeability transition (MPT) (Suzuki et al, 1999;Hail and Lotan, 2000;Poot et al, 2002;Boya et al, 2003), cytochrome c release (Suzuki et al, 1999;Asumendi et al, 2002;Boya et al, 2003), increased GADD153 (Kim et al, 2002;Lovat et al, 2002), and activation of 12-lipoxygenase (Lovat et al, 2002) or activation of c-Jun N-terminal kinase (JNK) (Chen et al, 1999;Shimada et al, 2002;Osone et al, 2004) have been implicated in 4HPR-mediated apoptosis in various cancer cells. In addition, retinoid receptors may contribute to 4HPR-induced apoptosis in some cells (Sun et al, 1999;Lovat et al, 2000;Ulukaya et al, 2003).…”
Section: Introductionmentioning
confidence: 99%